2019
DOI: 10.1155/2019/4738243
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Study on the Effects of Xiaoaiping on the Stemness of Hepatocellular Carcinoma Cells

Abstract: Aims. The aim of this study was to examine the effects of Xiaoaiping on the stemness of hepatocellular carcinoma (HCC) cells in vivo and to investigate the underlying molecular mechanism. Methods. A subcutaneous xenograft nude mouse model was established using Hep3B-derived HCC cells. The mice were randomly assigned to the 100 mg/kg Xiaoaiping or 100 μL/20 g normal saline (control) groups (n =3/sex/group) for daily intragastric administration for 14 days. The tumor size was closely monitored during the dosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…With an increasing number of clinical trials, it is urgent to systematically evaluate the efficacy of Xiaoaiping injection in the treatment of Hepatocellular carcinoma. [ 20 , 21 ] In this study, we will conduct systematic review and meta-analysis to provide more evidence on the effectiveness and safety for it. The findings of this study will provide helpful evidence for clinicians in the treatment of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an increasing number of clinical trials, it is urgent to systematically evaluate the efficacy of Xiaoaiping injection in the treatment of Hepatocellular carcinoma. [ 20 , 21 ] In this study, we will conduct systematic review and meta-analysis to provide more evidence on the effectiveness and safety for it. The findings of this study will provide helpful evidence for clinicians in the treatment of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 , 19 ] Studies have shown that Xiaoaiping injection can inhibit the growth of liver cancer and enhance the quality of life of patients with cancers. [ 20 , 21 ] The combination of Xiaoaiping injection and chemotherapies exerts an enhanced therapeutic effect against malignant tumors, and it does not increase the toxicity or side effects of chemotherapy. [ 18 , 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…As a stress response transcription factor widely expressed in various human tissues, HSF4 can promote cell proliferation and protect cell senescence [ ,, ], It has been reported that HSF4 can affect the function of caspase, which is beneficial to the survival of lens epithelial cells. Recent studies have found that the dysregulation of HSF4 is related to cancer, and it has been reported that HSF4 may promote cell proliferation and differentiation [ 6,7 ], Study also shows that the deletion of HSF4 is related to the increased expression of cyclin-dependent kinase inhibitors p21 and p27 in mouse embryonic fibroblasts 8 . HSF4 deletion suppressed Arf/P53mediated tumorigenesis through inhibiting proliferation and inducing cellular senescence in a P21 and P27-dependent manner 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that the dysregulation of HSF4 is related to cancer, and it has been reported that HSF4 may promote cell proliferation and differentiation [ 6,7 ], Study also shows that the deletion of HSF4 is related to the increased expression of cyclin-dependent kinase inhibitors p21 and p27 in mouse embryonic fibroblasts 8 . HSF4 deletion suppressed Arf/P53mediated tumorigenesis through inhibiting proliferation and inducing cellular senescence in a P21 and P27-dependent manner 8 . However, the regulatory role of HSF4 in liver cancer stemness properties remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Wight et Arn ., was approved by the China Food and Drug Administration (CFDA) for tumor treatment with approval number Z20025868. It has exhibited antitumor effects on various cancers such as ovarian cancer, [ 11 , 12 ] esophageal cancer, [ 13 ] gastric cancer, [ 14 ] lung cancer, [ 15 , 16 ] liver cancer, [ 17 , 18 ] and breast cancer. [ 19 , 20 ]…”
Section: Introductionmentioning
confidence: 99%